A Bi2S3-embedded gellan gum hydrogel for localized tumor photothermal/antiangiogenic therapy. Issue 14 (31st March 2021) - Wu, Yingjiao; Liang, Yuqing; Liu, Yandi; Hao, Yijun; Tao, Na; Li, Juan; Sun, Xiaoyi; Zhou, Ming; Liu, You-Nian
Abstract : Bi2 S3 @GG nanocomposite hydrogel was prepared through a one-pot synthesis method using gellan gum as a stabilizer, and then designed for the combination of photothermal and antiangiogenic therapy. Abstract : An injectable gellan gum-based nanocomposite hydrogel (Bi2 S3 @GG) was designed for X-ray computed tomography (CT) imaging and photothermal/antiangiogenic therapy. The linear anionic polysaccharide gellan gum (GG) was used as a stabilizer, embedded with ultra-small bismuth sulfide (Bi2 S3 ) nanodots (∼2 nm) through a one-pot synthesis method. The as-prepared Bi2 S3 @GG hydrogel displays excellent capability for both photothermal therapy (PTT) (with a photothermal conversion efficiency of 44.3%) and X-ray computed tomography (with an X-ray absorption coefficient of 51.5 HU L g −1 ), integrated with real-time monitoring drug retention and tunable therapeutic functions. After the incorporation of sorafenib (SF), the hydrogel shows a sustained release of SF over 15 days. A tumor suppression rate of 98.2% is shown at day 22 postinjection in the mice received the combined treatments of photothermal/antiangiogenic therapy. In contrast, tumor growth and recurrence are observed in the single treatment. Our work presents a new strategy to construct a multifunctional hydrogel platform for a safe and precise antitumor therapy.